1947
DOI: 10.1084/jem.85.1.99
|View full text |Cite
|
Sign up to set email alerts
|

The Nucleic Acid and Carbohydrate of Influenza Virus

Abstract: Both ribonucleic and desoxyribonucleic acids have been obtained from purified particles of PR8 influenza virus. These particles were also found by extraction with formamide to contain carbohydrate in addition to that of the nucleic acids. Carbohydrate-rich fractions, essentially devoid of nucleic acid, were obtained not only from the particles representing PR8 virus but from those of Lee influenza virus as well. The carbohydrate in each case appeared to be a polysaccharide composed of mannose, galactose, and g… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
10
0

Year Published

1947
1947
2008
2008

Publication Types

Select...
4
2
1

Relationship

0
7

Authors

Journals

citations
Cited by 57 publications
(10 citation statements)
references
References 30 publications
(56 reference statements)
0
10
0
Order By: Relevance
“…Though Knight (1947) found that a sample of nucleic acid isolated from defatted virus was degraded by crystalline ribonuclease, specific chemical evidence has been obtained only recently. As judged by absorption measurements at 260 mp.…”
mentioning
confidence: 99%
“…Though Knight (1947) found that a sample of nucleic acid isolated from defatted virus was degraded by crystalline ribonuclease, specific chemical evidence has been obtained only recently. As judged by absorption measurements at 260 mp.…”
mentioning
confidence: 99%
“…The Public Health Laboratory, Northampton (With 4 Figures in the Text) Early estimations of the nucleic acid content of influenza virus A gave values of the order of 5 % and indicated the probable presence of both ribonucleic acid (RNA) and deoxyribonucleic acid (DNA) (Taylor, 1944;Knight, 1947;Graham, 1950).…”
Section: By W Frisch-niggemeyer and L Hoylementioning
confidence: 99%
“…Taylor (1944) and Knight (1947) showed that influenza virus preparations contained carbohydrate other than nucleic acid sugar. By the use of the carbazole colour reaction Knight suggested that the carbohydrate was made up of galactose, mannose and glucosamine units.…”
Section: Nucleic Acid Content Of Intact Virusmentioning
confidence: 99%
“…There are sixteen amino acids in all (Knight, 1947), the major one being arginine 9-8 per cent, the others are lysine 1-47 per cent, aspartic acid 13-5 per cent, glutamic acid 11-3 per cent, which accounts for the acidity of the protein, cysteine (no cystine) 0-69 per cent, glycine 1-9 per cent, isoleucine &6 per cent, leucine 9-3 per cent, phenylalanine 8 -4 per cent, proline 5-8 per cent, serine 7-2 per cent, threonine 9-9 per cent, tryptophane 2-1 per cent, tyrosine 3-8 per cent, valine 9-2 per cent.…”
Section: Tobacco Mosaic Virusmentioning
confidence: 99%
“…Investigations on highly purified preparations of influenza virus have revealed the presence of an amount of carbohydrate apparently greater than that accountable for in the nucleic acids. Knight (1947) obtained carbohydrate-rich fractions from highly purified samples of PR 8 and Lee influenza viruses and subjected them to analysis. In each case, the carbohydrate appeared to be a polysaccharide composed of mannose, galactose, and glucosamine units.…”
Section: Influenza Virusmentioning
confidence: 99%